2020
DOI: 10.1016/j.cpet.2019.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis, Staging, Radiation Treatment Response Assessment, and Outcome Prognostication of Head and Neck Cancers Using PET Imaging

Abstract: Diagnosis: 18 F-FDG PET/CT is recommended before pan-endoscopy or other invasive procedures in the workup for head and neck squamous cell carcinoma (HNSCC) of unknown primary. Staging: 18 F-FDG PET/CT is recommended in patients with locoregionally advanced HNSCC given its high level of accuracy in detecting nodal disease and sensitivity for distant metastases. Radiation treatment response: 18 F-FDG PET/CT at 12 weeks after completion of definitive chemoradiation negates the need for planned neck dissection in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…18 F-fluorodeoxyglucose ( 18 F-FDG) positron-emission tomography (PET) is a widely used tool for staging, planning, and monitoring HNC, identifying both morphological and metabolic abnormalities within the tumor. [8][9][10] Lately, many easily obtainable PET parameters and their prognostic relevance in HNC are being studied. Maximum standardized uptake value (SUVmax) is a measurement widely used in clinical practice; nonetheless, many studies show conflicting results concerning its usefulness.…”
Section: Introductionmentioning
confidence: 99%
“…18 F-fluorodeoxyglucose ( 18 F-FDG) positron-emission tomography (PET) is a widely used tool for staging, planning, and monitoring HNC, identifying both morphological and metabolic abnormalities within the tumor. [8][9][10] Lately, many easily obtainable PET parameters and their prognostic relevance in HNC are being studied. Maximum standardized uptake value (SUVmax) is a measurement widely used in clinical practice; nonetheless, many studies show conflicting results concerning its usefulness.…”
Section: Introductionmentioning
confidence: 99%
“…To date the 2-deoxy-2-[18F]fluoro-D-glucose (FDG) positron emission tomography/computed tomography (PET/CT) is a standard diagnostic methodic used in HNC patients for staging, restaging, RT planning, and outcome evaluation (37,38). Several data published in literature underline how changes of neoplastic glucose metabolism, evaluated by FDG PET, are able to predict tumor response rates and oncological outcomes in several solid cancer (39). In particular as regards PET in HNC the major data are validated for SCCHN and nasopharyngeal cancer.…”
Section: Role Of Molecular Imaging In Researchmentioning
confidence: 99%
“…In this settings, PET/CT could help radiation oncologist for target delineation and in radiation planning (39). Moreover, it has been suggested that FDG is able to detect primary tumor site in about 25% of patients with unknown disease (40) and at baseline, it allows quantification of the tumor tracer uptake thus producing semiquantitative values that can be indicative of prognosis.…”
Section: Role Of Molecular Imaging In Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of detecting the tumour and defining tumour cells with radioresistance was evaluated implementing different hypoxia-delineating radiotracers, namely [ 18 F]-FMISO, [ 18 F]-FAZA and [ 18 F]-HX4. For all three tracers, the tracer uptake correlated with the grade of hypoxia in the viable tumour cells [14]. Especially molecular imaging using the most promising hypoxia-related radiotracer [ 18 F]-HX4, it effectively demonstrates changes in hypoxia by detecting the extent of hypoxic cells in the tumour volume during radiotherapy [15].…”
mentioning
confidence: 99%